x(3x-2)+x(4x-2)=(7x+8)(x-4)

Simple and best practice solution for x(3x-2)+x(4x-2)=(7x+8)(x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(3x-2)+x(4x-2)=(7x+8)(x-4) equation:


Simplifying
x(3x + -2) + x(4x + -2) = (7x + 8)(x + -4)

Reorder the terms:
x(-2 + 3x) + x(4x + -2) = (7x + 8)(x + -4)
(-2 * x + 3x * x) + x(4x + -2) = (7x + 8)(x + -4)
(-2x + 3x2) + x(4x + -2) = (7x + 8)(x + -4)

Reorder the terms:
-2x + 3x2 + x(-2 + 4x) = (7x + 8)(x + -4)
-2x + 3x2 + (-2 * x + 4x * x) = (7x + 8)(x + -4)
-2x + 3x2 + (-2x + 4x2) = (7x + 8)(x + -4)

Reorder the terms:
-2x + -2x + 3x2 + 4x2 = (7x + 8)(x + -4)

Combine like terms: -2x + -2x = -4x
-4x + 3x2 + 4x2 = (7x + 8)(x + -4)

Combine like terms: 3x2 + 4x2 = 7x2
-4x + 7x2 = (7x + 8)(x + -4)

Reorder the terms:
-4x + 7x2 = (8 + 7x)(x + -4)

Reorder the terms:
-4x + 7x2 = (8 + 7x)(-4 + x)

Multiply (8 + 7x) * (-4 + x)
-4x + 7x2 = (8(-4 + x) + 7x * (-4 + x))
-4x + 7x2 = ((-4 * 8 + x * 8) + 7x * (-4 + x))
-4x + 7x2 = ((-32 + 8x) + 7x * (-4 + x))
-4x + 7x2 = (-32 + 8x + (-4 * 7x + x * 7x))
-4x + 7x2 = (-32 + 8x + (-28x + 7x2))

Combine like terms: 8x + -28x = -20x
-4x + 7x2 = (-32 + -20x + 7x2)

Add '-7x2' to each side of the equation.
-4x + 7x2 + -7x2 = -32 + -20x + 7x2 + -7x2

Combine like terms: 7x2 + -7x2 = 0
-4x + 0 = -32 + -20x + 7x2 + -7x2
-4x = -32 + -20x + 7x2 + -7x2

Combine like terms: 7x2 + -7x2 = 0
-4x = -32 + -20x + 0
-4x = -32 + -20x

Solving
-4x = -32 + -20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '20x' to each side of the equation.
-4x + 20x = -32 + -20x + 20x

Combine like terms: -4x + 20x = 16x
16x = -32 + -20x + 20x

Combine like terms: -20x + 20x = 0
16x = -32 + 0
16x = -32

Divide each side by '16'.
x = -2

Simplifying
x = -2

See similar equations:

| -7+5m+6=-27 | | 3(2x+7)=7-2(x-7) | | 3-10(x)=127 | | 2r+2=-3r-5+5 | | 4/3*3.14*5^3 | | n+14=6 | | -5k-3=-33 | | f(x)=3x-1/x^3 | | 3x-7x+8=2/3 | | y=140/x | | (x-8)(x-8)-1=0 | | -0.28p-0.06(2-6p)=0.06(p-2)-0.1 | | f(x)=5x^4+3x+7 | | 12,000/52=x/1 | | 104+8x=107+7x | | 79+9x=94+4x | | 2(6+-7x+2x^2)=0 | | 10-.33333y=4+6x | | 9q^2+9q-10=0 | | 49=7j | | 4+5w-4w=4-2 | | z-7=36 | | 2-(1/4) | | (5x)+(x+20)+(2x)=180 | | 4+9(x)=184 | | (9*sqr-1)8(-6*sqr-4)= | | 20=x-4 | | w-50=16 | | -14=(6/7)x-4-7x | | (9*((-1)^1/2)*((-6)((-4)^1/2))= | | 6x-7=1+4x | | 47=p+14 |

Equations solver categories